Couples-focused intervention to improve engagement in HIV care: protocol for a randomised controlled trial - Torsten B Neilands; Alyssa Paige Tabrisky; Lara S Coffin; David P Olem (BMJ Open)
Introduction Advances in HIV treatment have proven to be effective in increasing virological suppression, thereby decreasing morbidity, and increasing survival. Medication adherence is an important factor in reducing viral load among people living with HIV (PLWH) and in the elimination of transmission of HIV to uninfected partners. Achieving optimal medication adherence involves individuals taking their medications every day or as prescribed by their provider. However, not all PLWH in the USA are engaged in care, and only a minority have achieved suppressed viral load (viral load that is lower than the detectable limit of the assay). Sexual and gender minorities (SGM; those who do not identify as heterosexual or those who do not identify as the sex they were assigned at birth) represent a high-risk population for poor clinical outcomes and increased risk of HIV transmission, as they face barriers that can prevent optimal engagement in HIV care. Research in dyadic support, specifically within primary romantic partnerships, offers a promising avenue to improving engagement in care and treatment outcomes among SGM couples. Dyadic interventions, especially focused on primary romantic partnerships, have the potential to have a sustained impact after the structured intervention ends.Methods and analysis This paper describes the protocol for a randomised control trial of a theory-grounded, piloted intervention (DuoPACT) that cultivates and leverages the inherent sources of support within primary romantic relationships to improve engagement in HIV care and thus clinical outcomes among persons who are living with HIV and who identify as SGM (or their partners). Eligible participants must report being in a primary romantic relationship for at least 3 months, speak English, at least one partner must identify as a sexual or gender minority and at least one partner must be HIV+ with suboptimal engagement in HIV care, defined as less than excellent medication adherence, having not seen a provider in at least the past 8 months, having a detectable or unknown viral load or not currently on antiretroviral therapy. Eligible consenting couples are allocated equally to the two study arms: a structured six-session couples counselling intervention (DuoPACT) or a three-session individually-delivered HIV adherence counselling intervention (LifeSteps). The primary aim is to evaluate the efficacy of DuoPACT on virological suppression among HIV+ members of SGM couples with suboptimal engagement in care. The DuoPACT study began its target enrolment of 150 couples (300 individuals) in August 2017, and will continue to enrol until June 2021.Ethics and dissemination All procedures are approved by the Institutional Review Board at the University of California, San Francisco. Written informed consent is obtained from all participants at enrolment, and study progress is reviewed twice yearly by an external Safety Monitoring Committee. Dissemination activities will include formal publications and report back sessions with the community.Trial registration number NCT02925949; Pre-results.